2021
DOI: 10.1253/circj.cj-20-0877
|View full text |Cite
|
Sign up to set email alerts
|

Esm1 and Stc1 as Angiogenic Factors Responsible for Protective Actions of Adipose-Derived Stem Cell Sheets on Chronic Heart Failure After Rat Myocardial Infarction

Abstract: he efficacy of pharmacological and surgical treatments for chronic heart failure after myocardial infarction (MI) is limited. Cell-based regenerative therapy (cell transplantation) improved the blood supply to the damaged heart, and minimized the area of infarc-tion. 1-3 These beneficial effects are mediated, in part, by cytokines, such as hepatocyte growth factor (HGF) and Editorial p ????

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Lin et al [40] and Wuest et al [41] found that the role of IL1RL1 and ALOX15B in coronary artery disease. Research have shown that SERPINA3 [42], GPR78 [43] and ESM1 [44] plays a significant role in MI progression. Expression of the SCGN (secretagogin, EF-hand calcium binding protein) gene plays a role in the development of diabetes mellitus [45], but this genes might be novel target for MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al [40] and Wuest et al [41] found that the role of IL1RL1 and ALOX15B in coronary artery disease. Research have shown that SERPINA3 [42], GPR78 [43] and ESM1 [44] plays a significant role in MI progression. Expression of the SCGN (secretagogin, EF-hand calcium binding protein) gene plays a role in the development of diabetes mellitus [45], but this genes might be novel target for MI.…”
Section: Discussionmentioning
confidence: 99%
“…PLA2G2A [61], CCL23 [62], CD53 [63], TREML4 [64], TREM2 [65], CD180 [66], HPSE (heparanase) [67], CELA2A [68], TNFRSF4 [69], AMBP (alpha-1-microglobulin/bikunin precursor) [70], SOX18 [71], PANX2 [72], RSPO2 [73], COMP (cartilage oligomeric matrix protein) [74], ASGR1 [75] and NOXA1 [76] are involved in progression of atherosclerosis. A previous study reported that S100A9 [77], ADORA3 [78], IL1R2 [79], FPR1 [80], CCL20 [81], CD163 [82], S100A8 [83], TLR2 [84], HAS2 [85], PTX3 [86], TIMP4 [87], AREG (amphiregulin) [88], LBP (lipopolysaccharide binding protein) [89], IL18R1 [90], ALOX5AP [91], RETN (resistin) [92], F13A1 [93], FPR2 [94], SAA1 [95], FLT3 [96], AQP4 [97], FCER1G [98], CCL18 [99], HP (haptoglobin) [100], CDK1 [101], SLC7A11 [102], CFTR (CF transmembrane conductance regulator) [103], F8 [104], STC1[44], IL18RAP [90], TIMP3 [105], PDE4D [106], CYP4A11 [107], SCN10A [108], APOB (apolipoprotein B) [109], ACE (angiotensin I converting enzyme) [110], PENK (proenkephalin) [111], HSPB6 [112], TLR9 [113], EGR1 [114], CACNG8 [115], FOXD3 [116], DBH (dopamine beta-hydroxylase) [117], FOXP3 [118], GLP1R [119], IL34 [120], CCN1 [121], ADRA2A [122], BGN (biglycan) [123], NOS2 [124], AGRN (agrin) [125], DRD1 [126], GNB3 [127], EGR2 [128], MDK (midkine) [129], NOTCH3 [130], AZIN2 [131], NOTCH1 [132], LOX...…”
Section: Discussionmentioning
confidence: 99%
“…12 Watanabe et al have created dual reporter transgenic rats expressing green fluorescence protein and luciferase and fabricated ADSC sheets using a temperature-responsive culture dish. 13 When these ADSC sheets were implanted in the rat model of myocardial infarction, tracking of luciferase signals revealed that the implanted ADSC sheets survived for ≥2 weeks after implantation. After ADSC sheet implantation, there was an increase in microvessels in the ischemic area, and cardiac function after myocardial infarction improved.…”
mentioning
confidence: 99%
“…After ADSC sheet implantation, there was an increase in microvessels in the ischemic area, and cardiac function after myocardial infarction improved. 13 Thus, ADSC sheet implantation may allow cells to survive for a relatively long time and for them to perform their functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation